The Bolivian universal health system and effective access to healthcare: A diagnosis - Gabriela Alondra Agafitei (Institute for Advanced Development Studies (INESAD), 2022)
In 2019, the Bolivian government began implementation of the Universal Health Insurance (SUS) scheme, with critics claiming the unpreparedness of the healthcare system to provide universal and free services. To date, there is no research that assesses the effects of the reform and to what extent it is providing universal, free services. The objective of this study is to fill this research gap by providing a diagnosis on access to public healthcare services after the SUS's adoption. In this study, access is operationalized according to a theoretical framework developed by the World Health Organization (2010). The study has been conducted according to a combined method that compares data from before and after the SUS approval. First, data from the National Household Survey has been analyzed to provide an overview of dimensions related to access at the macro level. Secondly, the macro perspective is integrated with data collected through semi-structured interviews that provide a detailed analysis of the qualitative dimensions of accessing healthcare at the micro level, which are often not reflected by quantitative indicators. The results showed that on the one hand access to public healthcare services has increased in the first year of the SUS's implementation compared to previous years. However, despite the supply of additional human resources and physical infrastructure, the sufficiency in availability of human resources remains questionable, as the values disaggregated per 1,000 inhabitants remained roughly the same. Similarly, spending at the macroeconomic level did not reach recommended levels for universal coverage. Data from the case study deepens the understanding of the findings at the macro level. In fact, access appears as characterized by considerable challenges, such as long waiting times, lack of medicines and of beds, and low-quality services that overall restrain access to the public services. The study has concluded that despite the fact that access has increased, insufficiency of resources and the structural characteristics of the Bolivian healthcare system represent severe limitations for the universal outreach of SUS.
Keywords: I18; J18; D63; 330; Universal healthcare; effective access; coverage; insurance